Synthesis of Polymer Bioconjugates via Photoinduced Atom Transfer Radical Polymerization under Blue Light Irradiation - Fu, Liye (ACS Macro Lett, 2018)
A rapid blue-light-induced atom transfer radical polymerization (ATRP) was conducted in a biologically friendly environment. Well-controlled polymerization of oligo(ethylene oxide) methyl ether methacrylate (OEOMA) was successfully performed in aqueous media (1X PBS) under irradiation by blue LED strips. With 10.0 mW/cm(2) intensity output at 450 nm, >90% conversion was achieved in 2 h in the presence of a system comprising glucose, glucose oxidase, and sodium pyruvate. Poly-(OEOMA) was synthesized with predetermined M(n) and low dispersities using low ppm of Cu catalysts. Importantly, secondary structures of proteins, as analyzed by circular dichroism (CD), were preserved under blue-light irradiation due to its lower energy output. The aqueous blue-light ATRP technique was applied to biological systems by synthesizing well-defined protein—polymer and DNA-polymer hybrids by the “grafting-from” method.